Comparative Analysis of the Determinant Factors of Return on Assets between Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) - Lucky Nugroho; Akhmad Amien Mastur; Ulfa Ulfa; Tri Wahyono; Soeharjoto Soeharjoto (Jurnal Economia, 2021)
Abstract: This study aimed to analyze and compare the factors that affect the return on assets (ROA) of Islamic commercial banks (BUS) and Islamic business units (UUS). This study’s independent variables are NPF, FDR, and MSMEs. The study used the quantitative method, with multiple regression approaches in analyzing the research data. The results of this study show that the BUS NPF has a negative and significant impact on the BUS ROA; the BUS FDR has a positive and insignificant impact on the BUS ROA; the BUS MSMEs  portion of the BUS loan distribution has a negative and insignificant impact on the BUS ROA; the UUS NPF has a negative and significant impact on the UUS ROA; the UUS FDR has a positive and significant impact on the UUS ROA; and the MSMEs’ portion of the UUS loan distribution has a positive and significant impact on the UUS ROA.Keywords: BUS, UUS, Return on Asset, Non-Performing Financie, Financing to Deposit Ratio, MSME financing Analisis Perbandingan Determinan Faktor Return on Asset antara Bank Umum Syariah (BUS) dengan Unit Usaha Syariah (UUS)Abstrak: Penelitian ini bertujuan untuk menganalisa perbandingan variabel-variabel yang mempengaruhi return on asset pada Bank Umum Syariah (BUS) dengan Unit Usaha Syariah (UUS). Adapun variable-variabel bebas yang digunakan pada penelitian ini adalah non performing financing, financing to deposit ratio dan porsi penyaluran pinjaman usaha mikro, kecil dan menengah (UMKM). Metode yang digunakan adalah kuantitatif dengan pendekatan regresi berganda dalam melakukan analisa penelitian ini. Hasil dari penelitian ini diketahui bahwa NPF BUS berdampak negatif dan signifikan terhadap  ROA BUS; FDR BUS berdampak postif dan tidak signifikan terhadap ROA BUS; porsi penyaluran pinjaman UMKM BUS berdampak negatif dan tidak signifikan terhadap ROA BUS; NPF UUS berdampak negatif dan signifikan terhadap ROA UUS; FDR UUS berdampak positif dan signifikan terhadap ROA UUS; Porsi penyaluran pinjaman UMKM UUS berdampak positif dan signifikan terhadap ROA UUS.Kata kunci: BUS, UUS, ROA, NPF, FDR, Pembiayaan UMKM